2020
DOI: 10.1039/c9np00052f
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting of the DEAD-box RNA helicase eukaryotic initiation factor (eIF) 4A by natural products

Abstract: This highlight reviews natural products targeting of the eIF4A RNA helicase by interfering with RNA-binding or acting as interfacial inhibitors to increase RNA resident time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…The rocaglates target the translation initiation factor eIF4A in C. auris. Rocaglates have been reported to inhibit translation initiation in mammalian cells and S. cerevisiae through interaction with orthologues of the eukaryotic initiation factor 4A (eIF4A) (30)(31)(32)(33). In examining the rocaglates present in the BU-CMD collection, we found that all four hit rocaglates are among the strongest enhancers of human eIF4A1-polypurine RNA clamping (34), further supporting the identification of translation as a putative target.…”
Section: Resultsmentioning
confidence: 58%
“…The rocaglates target the translation initiation factor eIF4A in C. auris. Rocaglates have been reported to inhibit translation initiation in mammalian cells and S. cerevisiae through interaction with orthologues of the eukaryotic initiation factor 4A (eIF4A) (30)(31)(32)(33). In examining the rocaglates present in the BU-CMD collection, we found that all four hit rocaglates are among the strongest enhancers of human eIF4A1-polypurine RNA clamping (34), further supporting the identification of translation as a putative target.…”
Section: Resultsmentioning
confidence: 58%
“…There are three natural products that can be combined with EIF4A, including hippuristanol, pateamine A and rocaglates (41). Hippuristanol displays decreased effectiveness toward EIF4A3, requiring 10-fold higher concentrations compared with EIF4A1/2 (42).…”
Section: Eif4a3 Inhibitorsmentioning
confidence: 99%
“…To date, several small molecules have been identified that selectively target DDX/DHX-box helicase family members, and these have been extensively reviewed in [163] (summarized in Table 2). In brief, helicase inhibitors can be stratified into two groups: (i) interfacial inhibitors, in which the compounds interact with both the protein target and the RNA, and (ii) compounds that inhibit RNA binding.…”
Section: Targeting Ddx/dhx-box Helicases In Translation Initiationmentioning
confidence: 99%